Manajemen Sekolah Biasa Menjadi Sekolah Rujukan di SMP Negeri 1 Ujan Mas Kabupaten Kepahiang - Hamengkubuwono Hamengkubuwono (Edukasi Islami : Jurnal Pendidikan Islam, 2022)
The implementation of education must meet national education standards, and it is even demanded to be more than that is required. Therefore, school administrators must manage their schools to become superior and competitive schools. However, the limitations of various supporting capacities cause schools not to run optimally. In this study, the state junior high school 1 Ujan Mas, Kepahiang Regency, has been an impact school for learning about quality school management. Management of an ordinary school into a reference school goes through some phases of activities starting from preparation, planning, organizing, coordinating, implementing, to evaluation.